Pavement condition information management employing GIS and UAV - Mamani Quenallata, Frady Wilson (2023)
The research proposes an efficient means to manage information on the condition, type and maintenance actions of pavements through the geographic information system (GIS). For its development, Quantum GIS (QGIS) was used, in which a database of 3 090,8 m of pavement was created. In addition, the information on the condition of the pavements was recorded using the ASTM D 6433-07 evaluation sheet. The inventory of failures was carried out by visual inspection in situ and by taking images assisted by an unmanned aerial vehicle (UAV). The results obtained using the GIS and UAV in the evaluation of pavements show that the efficiency in relation to the conventional method in time and cost is 27,3 % and 24,9 % respectively. On the other hand, there is no significant difference in the values of the condition index between both methods. In conclusion, with the use of GIS and UAV, efficient and structured management is made. Consequently, the results of the condition of the pavement are obtained much faster and cheaper than the traditional evaluation. In the same way, this proposal allows monitoring, and making optimal decisions in the post-construction, maintenance and rehabilitation phases.